Impact of the Global Financial Crisis on Exchange Rates and Policies in Sub-Saharan Africa - Kaendera, Stella (Departmental Papers; Departmental Paper ;, 2009)
This paper studies the evolution of the exchange rates of sub-Saharan African currencies in the context of the global financial crisis. In particular, it analyzes the reasons behind the differences in the magnitude and volatility of the exchange rates among countries. To this end, it takes a sample of seven countries, four members of the East African Community (EAC) (Kenya, Rwanda, Tanzania, and Uganda), and three others, which experienced large exchange rate losses at the onset of the crisis: Ghana, Nigeria, and Zambia. First, it analyzes the movements of the exchange rates with respect to the U.S. dollar and two other major currencies. Second, it tries to link the magnitude of their movements to key factors, relating to the external environment and the countries' internal policies.